2017
DOI: 10.1038/srep40774
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic modifications at DMRs of placental genes are subjected to variations in normal gestation, pathological conditions and folate supplementation

Abstract: Invasive placentation and cancer development shares many similar molecular and epigenetic pathways. Paternally expressed, growth promoting genes (SNRPN, PEG10 and MEST) which are known to play crucial role in tumorogenesis, are not well studied during placentation. This study reports for the first time of the impact of gestational-age, pathological conditions and folic acid supplementation on dynamic nature of DNA and histone methylation present at their differentially methylated regions (DMRs). Here, we repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 91 publications
(56 reference statements)
0
21
0
1
Order By: Relevance
“…1–3). Previous studies carried out in our lab 43 and other studies 44,45 have reported that deficiency of folate can lead to an increase in intestinal uptake of folate thereby increasing the expression of folate transporters.…”
Section: Discussionmentioning
confidence: 66%
“…1–3). Previous studies carried out in our lab 43 and other studies 44,45 have reported that deficiency of folate can lead to an increase in intestinal uptake of folate thereby increasing the expression of folate transporters.…”
Section: Discussionmentioning
confidence: 66%
“…Prenatal phthalate exposures have also been linked to altered DNA methylation patterns in both human placenta [ 80 ] and cord blood [ 81 ], and the effects of phthalate exposures on asthma are thought to be mediated through DNA methylation alterations [ 82 ]. Similarly, folic acid and other B-vitamins that are contained at high concentrations in prenatal vitamins are essential for DNA methylation reactions [ 83 , 84 ], and prenatal folate is associated with altered placental [ 85 ] and cord DNA methylation [ 86 ]. Examining effect modification by specific nutrients could shed light on potential mechanisms involved.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, DMRs may be present in the promoter of a gene controlling its expression, according to the methylation status. This happens with MEST/PEG1 and PEG10 genes that are paternally expressed and located on the long arm of the chromosome 7 [25][26][27].…”
Section: Introductionmentioning
confidence: 99%